Long-term cardiovascular and cerebrovascular morbidity in Israeli thyroid cancer survivors - Elena Izkhakov; Joseph Meyerovitch; Micha Barchana; Yacov Shacham; Naftali Stern; Lital Keinan-Boker (Endocrine Connections, 2019)
Objective: Thyroid cancer (TC) survivors may be at risk of subsequent cardiovascular and cerebrovascular (CaV&CeV) morbidity. The 2009 American Thyroid Association (ATA) guidelines recommended less aggressive treatment for low-risk TC patients. The aim of this study was to assess the atherosclerotic CaV&CeV outcome of Israeli TC survivors compared to individuals with no thyroid disease, and the atherosclerotic CaV&CeV outcome before (2000–2008) and after (2009–2011) implementation of the 2009 ATA guidelines. Methods: All members of the largest Israeli healthcare organization who were diagnosed with TC from 1/2000 to 12/2014 (study group) and age- and sex-matched members with no thyroid disease (controls) were included. Adjusted hazard ratios (HRs) and 95% confidence intervals (95% CIs) were calculated using Cox proportional hazards models. Results: The mean follow-up was 7.6 ± 4.2 and 7.8 ± 4.1 years for the study (n = 5,677, 79% women) and control (n = 23,962) groups, respectively. The former had an increased risk of new atherosclerotic CaV&CeV events (adjusted HR 1.26, 95% CI 1.15–1.39). The 5-year incidence of CaV&CeV was lower (adjusted HR 0.49, 95% CI 0.38–0.62) from 2009 to 2011 compared to 2000 to 2008, but remained higher in the study group than in the control group (adjusted HR 1.5, 95% CI 1.14–1.69). Conclusions: This large Israeli population-based cohort study showed greater atherosclerotic CaV&CeV morbidity in TC survivors compared to individuals with no thyroid diseases. There was a trend toward a decreased 5-year incidence of atherosclerotic CaV&CeV events among TC survivors following the implementation of the 2009 ATA guidelines, but it remained higher compared to the general population.